Cardiac resynchronization therapy: long-term impact of echocardiographic non-progression. (19th May 2022) - Monteiro, E; Madeira, M; Antonio, N; Marinho, V; Milner, J; Sousa, P; Ventura, M; Cristovao, J; Elvas, L; Goncalves, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: As heart failure (HF) is a progressive disease, there has been a raising idea that considering the absence of echocardiographic improvement as non-response to cardiac resynchronization therapy (CRT) may not be appropriate. In fact, in some classical echocardiographic non-responders, CRT might have prevented HF deterioration. Purpose: Our aim was to compare the composite outcome of death and re-admissions due to HF according to a new classification of CRT response: responders, non-progressors and progressors. Methods: We included 144 consecutive patients with HF, left ventricle (LV) ejection fraction < 40% and QRS duration > 120mseg submitted to CRT implantation. Patients were divided into 3 groups according to the variation of LV end-systolic volume (LVESV) at 6-month: ≥15% reduction in LVESV - responders (R); 0–15% reduction in LVESV – non-progressors (NPr); increase in LVESV – progressors (Pr). A long-term follow-up (4.9 ± 2.9 years) was performed targeting mortality and re-admissions due to HF. Results: In our population, 78 patients (54.2%) were classified as R, 21 (14.5%) as NPr and 45 (31.3%) as Pr. Baseline comparison between groups is presented in table 1. Compared with R, N-Pr had ischemic aetiology more frequently. The prescription of digoxin was more common in Pr. The Kaplan-Meier curves (figure 1) demonstrate that the composite outcome of death and re-admission due to HF had a lower incidence in R, but was similar between N-Pr and Pr. After adjustment of possible confounders (ischemic aetiology and digoxin use), the type of response to CRT remained as the only predictor of outcomes (OR 0.61; CI 0.41-0.90). 144 Conclusion: In our population, patients without progression of HF had a similarly negative prognosis to the ones that deteriorated. Hence, positive LV remodelling, and not only stabilization seems to be necessary to improve long-term prognosis.